NEUTROPHIL-TO-LYPHOCYTE RATIO IS SIGNIFICANTLY INCREASED IN CENTRAL OBESITY - Muh Taufiq (Journal of Health, Technology and Science (JHTS), 2024)
The Neutrophil-to-Lymphocyte Ratio (NLR) is a biomarker closely associated with systemic inflammation, particularly in conditions like central obesity. Given that central obesity leads to increased NLR, which in turn raises the risk of metabolic syndrome, including cardiovascular disease, conducting this study is deemed highly necessary, especially in regions with a high prevalence of central obesity, such as Gorontalo City, Indonesia. This study was designed as a cross-sectional analysis. A total of 100 respondents, categorized as Central Obese (CO) and Non-Central Obese (Non-CO), were evaluated for their NLR. Obesity categories were assessed based on the Asia-Pacific criteria. Statistical analysis revealed significant differences in NLR between those with and without central obesity, for both men and women (with p-values of 0.020 and 0.004, respectively). Overall, the findings suggest that NLR is significantly higher in individuals with central obesity compared to those without. Future studies should focus on assessing the correlation between NLR and other metabolic disease risk factors.